Upper gastrointestinal foreign body: our experiences in rural area - Nishikant N. Gujar; Ashfak Ahmed R. Kakeri; Ashok Dhonde; A.N. Vishruth (Al Ameen Medical College, 2023)
Background: Foreign body ingestion is a common occurrence, particularly among children, but it can also affect adult patients. Objective: This case series study was to evaluate the presentation and outcome of accidentally ingested upper gastrointestinal foreign bodies. Material and Methods: The study included 45 patients with a history of ingested foreign body between January 2011 and June 2017 at the Dhonde Endoscopic and Laparoscopic Centre in Sangli. Results: The majority of cases (89%) were observed in the pediatric age group, with dysphagia being the most common presenting symptom (62.22%), followed by odynophagia (22.22%), drooling (11.11%), and a pricking sensation (4.45%). The cricopharynx and upper esophagus were identified as the most common sites of foreign body impaction, accounting for 97.8% of cases. Coins were found to be the predominant foreign bodies in children (90%), while mutton pieces were more common in older adults (40%). The management approach involved video gastroendoscopic retrieval, which was successful in the majority of cases. Only 8.88% of patients experienced complications, including chemical injury due to a button battery or pressure ulcer resulting from an impacted coin. Conclusion: Foreign body ingestion is a significant concern, especially in pediatric patients. Prompt and effective endoscopic retrieval can lead to favorable outcomes, with minimal complications. Awareness and understanding of foreign body ingestion can aid in timely intervention and improve patient outcomes.